Harnessing the potential of Achromobacter sp. M1 to remediate heavy metals from wastewater: genomic insights and environmental applications - Mahale, Mithil; Samson, Rachel; Dharne, Mahesh; Kodam, Kisan (Journal of Hazardous Materials, 2024)
Lead, mercury, and cadmium are classified as toxic under the toxic Substances' Priority List by CDC-ATSDR (Center for Disease Control-Agency for Toxic Substances and Disease Registry). This toxic trio is capable of disrupting the one-health harmony due to its human, animal, and environmental hazards. The present study aimed in removing the toxic trio within 24 h using a novel Achromobacter sp. M1. Atomic absorption spectroscopic evaluation for removal efficiency of Pb, Hg, and Cd by M1 was 68.8 +/- 0.9%, 82.7 +/- 1.9%, and 94.9 +/- 1.2 %, respectively, within 24 h. Lab-scale evaluation of strain M1 with wastewater showed the removal of the toxic trio together with the reduction in TSS from 140 to 118 ppm, BOD from 100 to 58 ppm, and COD from 381 to 222 ppm. Furthermore, strain M1 was capable of mitigating heavy metal stress and promoting plant growth, evidenced through chlorophyll, malondialdehyde, and proline estimation, together with the production of indole acetic acid (23.84 mu g/mL), siderophore (85 %), and solubilization of silica (39.66 mu g/mL). Whole genome sequencing revealed an ANI of 89 %, indicating a novel species of Achromobacter genus. A total of 23 putative genes for Cd, Hg, and Pb resistance were identified through genome mining.
Keywords: Achromobacter sp. M1; Metal biosorption; Metal transporters; Toxic trio; Whole genome